Why Projects Fail, from the Perspective of Service Science - Stanley, Ronald; Lorna, Uden (2017)
This article examines Project Failure in the IT Sector, specifically regarding projects being undertaken in organisations where project tasks clash for resources with concurrent regular ongoing “Business as Usual” IT operations. Projects also clash due to the project altering the organisational “status quo” in many other areas of the firm which are also causes of Project Failure which are examined. A background theoretical review of current Service Science thinking is undertaken, statement of current issues is made and then suggestions for areas of further research to attempt to address the issues from a Service Science perspective are discussed.